PERBEDAAN KADAR TRIGLISERIDA SERUM TIKUS SRAGUE DAWLEY PADA PEMBERIAN KOPI ROBUSTA FILTER DAN TANPA FILTER - Wahyani, Anggray Duvita; Kartini, Apoina (Journal of Nutrition College, 2012)
ABSTRACT Background: Dyslipidemia is a disorder of lipid metabolism characterized by (increasing or decreasing) lipid fraction disorders in blood plasma, such as triglyceride. Coffee is known as a bad effect coming from cafestol which can elevate triglyceride level on blood, nevertheless, it has positive effect coming from cafein which can decrease triglyseride level on blood.Method: true-experimental with pre-post randomized control groups design was conducted in this study. Subjects were 8 week-old and male Sprague Dawley rats which are given of filter and nonfilter robusta coffee’s  solution for 4 weeks. Serum-triglyceride levels are determined with GPO-PAP method. Normality data was examined by Shapiro Wilks. Data was analyzed with paired t-test and one way ANOVA.Result: This study showed the averages of pre triglycerides level in coffee filter are 99,67 mg/dl and post triglycerides level are 94,78 mg/dl (p=0,760). The averages of pre triglycerides level in unfilter coffee are 95,11 mg/dl and post triglycerides level are 91,33 mg/dl (p=0,693). Change averages of pre and post test in filtered coffee -4,89 mg/dl and unfiltered coffee -3,78 mg/dl (p=0,329).Conslusion: There were no differences in changes of triglyceride levels in the provision of robusta coffee filter and without filter Keywords: filter coffee, nonfilter coffee, trygliseride level, sprague dawley rats